Upaya Penurunan Waktu Set Up Mesin Die Cutting Dengan Menggunakan Metode Single Minute Exchange Die (Studi Kasus di Industri Paper Packaging) - Darmawan, Heru; Mustofa, Alvin Syaiful (DPPM UNIVERSITAS PELITA BANGSA, 2022)
Preparation in the production process is a must and many things must be done in the preparation process, because a good production process and good production results are determined by a good and correct preparation process. However, there is a negative effect from the set up which is the loss both in terms of time and in terms of product waste. It goes on the die cutting machine for 90 minutes with an average machine speed of 5000 pieces/hour so from this data there is still an opportunity to reduce the set up time so that losses due to set up time can be minimized. Therefore, we need a method that can reduce setup time and minimize losses due to long setup time. One method that can be used is Single Minute Exchange of Die (SMED). From the results of applying the SMED method to the die cutting machine, it was found that the setup time has been saved from 90 minutes to 60 minutes or there is a saving of 30 minutes. In addition, due to the improvement in the set up using dynamic stripping. , there is an increase in the cutting speed/hour of the die.cutting machine from 5000 cutting/hour before to 7000 cutting/hour or an increase of around 40%, as a result of the implementation of SMED there are of course many benefits obtained by the company directly and indirectly.